Evaluation of Developmental and Reproductive Fitness of Laboratory Selected Thiamethoxam Resistance in Black Legume Aphid Aphis craccivora Koch. - Routray, S.; Mishra, H. P. (International Journal of Bio-resource and Stress Management, 2021)
Thiamethoxam is a neonicotinoid group of insecticide which are selective agonists of the insect nicotinic acetylcholine receptor (nAChR), a pentameric cys-loop ligand-gated ion channel located in the central nervous system of insects. They provide farmers with invaluable, highly effective tools against some of the world’s most destructive crop pests. Black legume aphids, Aphis craccivora is one of the devastating polyphagous pests in agroecosystem and to manage their population, farmers are still relying on application of synthetic insecticides like Thiamethoxam. To evaluate the risk of resistance development, selection of A. craccivora was done to characterize Thiamethoxam resistance along with evaluation of developmental and reproductive fitness cost of the resistance. About 86.19 folds of resistance were developed after selecting for 24 generations. In the first twelve generations steady development of resistance was noticed followed by development become stiffer till 16th generation and more or less stable till 24th generations. Relative fitness of the selected resistant strain of aphids was decreased with longer nymphal duration and adult longevity. The mean nymphal duration was increased from 4.35±1.02 days (in F0) to 7.9±0.57 days (in F24). The fecundity rate was significantly less in resistant population (16.0±5.34) as compared to the susceptible strain (54.71±7.63) whereas, oviposition periods were significantly longer (12.49±1.44 days) in resistant population as compare to susceptible strain (9.50±1.22 days).